Assessing potential collateral effects on amphibians from insecticide applications for flea control and plague mitigation - David A. Eads; Susan A. Shriner; Jeremy W. Ellis; Paul M. Cryan; Michelle L. Hladik; Gregory P. Dooley; Erin Muths (PLoS ONE, 2025)
Ideal disease mitigation measures for wildlife are safe and benign for target species, non-target organisms, the environment, and humans. Identifying collateral (i.e., unintended) effects is a key consideration in implementing such actions. Deltamethrin dust and fipronil-laced baits represent a group of insecticides that target fleas (pulicides) and are used to control flea (Siphonaptera) vectors of the plague bacterium Yersinia pestis to protect prairie dogs (Cynomys spp.) and their plague-susceptible obligate predators, endangered black-footed ferrets (Mustela nigripes). A variety of animals use prairie dog burrows as refuge, which potentially exposes them to deltamethrin, and to fipronil and its metabolites in fecal pellets excreted by prairie dogs and other mammals that have eaten fipronil baits. We assessed the potential effects of deltamethrin and fipronil residues on survival, body mass, and activity of western tiger salamanders (Ambystoma mavortium), a burrow-inhabiting amphibian. Pulicides were applied at realistic concentrations in mesocosms mimicking burrows. Treatments included (1) deltamethrin dust and non-treated prairie dog fecal pellets, (2) prairie dog fecal pellets containing fipronil and fipronil sulfone, and (3) un-treated prairie dog fecal pellets as controls. All 29 salamanders survived the experiment. We did not detect pulicide residues in any control salamanders. Fipronil sulfone was detected in tissues from 3 of 10 salamanders in the fipronil treatment and deltamethrin was detected in tissues from 9 of 11 salamanders in the deltamethrin treatment. Salamanders were observed outside of burrows more frequently after treatments than before. Deltamethrin concentrations in whole body samples correlated positively with the amount of time salamanders were inside burrows. Acute, lethal effects were not detected, but uptake of deltamethrin and, to a lesser extent fipronil sulfone, into salamander tissues indicated the potential for long-term effects on this non-target species. Identifying potential collateral effects is an important aspect of evaluating mitigation actions implemented to protect endangered species.